Nalar Hikmah Dalam Fatwa Dsn-Mui Tentang Ganti Rugi (Ta’widh) - Ririh Ambarningsih; Achmad Nursobah; Anwar Ma’rufi (CV. ULIL ALBAB CORP, 2024)
In the context of Indonesia's economy and business, the practice of compensation (ta'widh) by Islamic financial institutions faces various issues and challenges. There are differing understandings and interpretations regarding the application of compensation in accordance with Sharia principles, with some views suggesting that the calculation methods and amounts of compensation are not yet fully compliant. This has led to dissatisfaction and controversy among customers. The practice of compensation is often misconstrued as a form of penalty, contradicting Sharia principles that prohibit usury. The goal of this study is to examine how Indonesian Islamic financial institutions have adopted the DSN-MUI fatwa on compensation, or ta'widh. The purpose of this qualitative study is to investigate the meanings and guiding principles of the fatwa provisions using a library research method and hikmah-based reasoning approach. Primary data is sourced from DSN-MUI fatwa documents, while secondary data includes academic literature. The analysis results indicate that the DSN-MUI fatwa effectively integrates the principles of hikmah, promoting justice, benefit, and adherence to Sharia. This fatwa enhances the implementation of ta'widh, ensuring consistency with core Sharia values, and contributes positively to the Islamic financial system. It is anticipated that the research findings would be used as a guide for Islamic financial institutions, regulators, and the general public in accurately implementing the fatwa in accordance with Sharia principles.